Pengaruh Brand Ambassador, Brand Image dan Korean Wave Terhadap Keputusan Pembelian Produk Skincare Scarlett Whitening: (Studi Kasus Mahasiswa Universitas Labuhanbatu) - Hani Ayuniatasya; Junita Lubis; Nur’ainun Gulo (BADAN PENERBIT STIEPARI PRESS, 2025)
The purpose of this study is to determine the influence of brand ambassadors, brand image, and korean wave on the purchase decision of scarlett whitening skincare products. This research is a quantitative research using questionnaires. The sample in this study was 84 respondents, namely 7 morning semester management students.this study used SPSS Version 22. The results of the study show that brand ambassadors have no and insignificant effect on purchase decisions, brand image has a positive and significant effect on purchasing decisions, and Korean waves have a positive and significant effect on purchase decisions. It can be seen from the results of the determination coefficient which is 34.9% while the remaining 65.1% is influenced by other factors that are not studied in this study.